الجوّ المفعم بالحيوية: نموذج التعليم التعاوني في تعليم اللغة العربية - Maulana, Muhammad Rifqi; Mahbubah, Latifatul (STIT Darul Hijrah Martapura, 2025)
In the increasingly dynamic world of education, cooperative learning comes as a bridge that connects knowledge with social skills through active collaboration among learners. This study aims to discuss the cooperative learning model in terms of its objectives, characteristics, elements, principles, and procedures. The research method used is a literature study with a content analysis approach. The results show that cooperative learning is a learning model that emphasizes cooperation among students in realizing learning objectives. This model focuses on students' cooperation in understanding learning materials in groups, which is one of its main characteristics. The characteristics of this model include group learning, acceptance of individual differences, and development of social skills. The elements of cooperative learning consist of positive dependence, individual responsibility, cooperation between group members, and group process evaluation. The principles of this model are divided into four, namely positive dependence, responsibility among group members, constructive confrontation, and effective cooperation and communication. The procedure for implementing this model includes material explanation by the teacher, group learning, evaluation, and recognition among group members.